Families, professionals, and exceptionality : positive outcomes through partnerships and trust - Turnbull, Ann P.; Turnbull, H. Rutherford ;Erwin, Elizabeth J. ;Soodak, Leslie C. ;Shogren, Karrie Ann (Upper Saddle River, New Jersey : Pearson, 2015)
The new edition retains the important aspects of the sixth edition in that it describes the family system theory, the history and current status policy, and the principles of partnership and their application by teachers and other professionals, plus cites of the most recent research, it also includes features.
Part 1. The Family systems perspective -- Part 2. History and public policy related to partnerships -- Part 3. Strategies and process for partnerships and desired outcomes.
Includes bibliographical references and index.
Keywords: COUNSELOR AND CLIENT